Adaptive Positioning Control of Multi-Point Moorings with Disturbance Observation Under Input Constraints - Run Lu; Guichen Zhang; Ru Liu; Chaojian Gao; Wei Chen; Huanglong Fu (Journal of Marine Science and Engineering)
In the presence of dynamic uncertainties, external time-varying disturbances, and limited inputs to the multi-point mooring system (MPMS) of a floating offshore platform (FOP), this paper proposes a robust adaptive dynamic surface (RADS) control method incorporating a disturbance observer. A disturbance observer is designed to estimate the unknown time-varying disturbance and apply feedforward compensation to the control variable. Simultaneously, the adaptive law of the σ-corrected leakage term is employed to estimate the bound of the disturbance observation error, thereby enhancing positioning accuracy. An auxiliary dynamic system (ADS) is then introduced to address input constraints, while the differential explosion problem associated with the traditional inversion method is resolved through the integration of the dynamic surface control (DSC) algorithm. The Lyapunov function is utilized to demonstrate that the controller ensures the consistent ultimate boundedness of all signals within the closed-loop system. Finally, a simulation experiment was conducted based on the eight-point mooring platform of the “Kantan3”, and the positioning accuracy reached 3%, which is higher than the specification requirements of the classification society. The results indicate that the designed controller achieves higher positioning accuracy and improved anti-interference performance and has been put into practical application on “Kantan3”.